2022
DOI: 10.1021/acsomega.2c03457
|View full text |Cite
|
Sign up to set email alerts
|

Simple Low Temperature Technique to Synthesize Sillenite Bismuth Ferrite with Promising Photocatalytic Performance

Abstract: Sillenite-type members of the bismuth ferrite family have demonstrated outstanding potential as novel photocatalysts in environmental remediation such as organic pollutant degradation. This investigation has developed a low temperature one-step hydrothermal technique to fabricate sillenite bismuth ferrite Bi 25 FeO 40 (S-BFO) via co-substitution of 10% Gd and 10% Cr in Bi and Fe sites of BiFeO 3 , respectively, by tuning hydrothermal reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Before including any photocatalyst in the dye solution, the self- decomposition rate of RhB was determined under identical conditions and only 4% RhB degradation was recorded aer 240 min, which is in good agreement with a previous study. 66 From the absorbance curve depicted in Fig. 9(a) and (b), it can be observed that the peak intensity of the spectra was reduced with respect to time following a hypsochromic shi, which indicates the deterioration of RhB solution under the UVvis spectrum due to the inclusion of CSB and CSB ′ B samples, respectively.…”
Section: Papermentioning
confidence: 93%
“…Before including any photocatalyst in the dye solution, the self- decomposition rate of RhB was determined under identical conditions and only 4% RhB degradation was recorded aer 240 min, which is in good agreement with a previous study. 66 From the absorbance curve depicted in Fig. 9(a) and (b), it can be observed that the peak intensity of the spectra was reduced with respect to time following a hypsochromic shi, which indicates the deterioration of RhB solution under the UVvis spectrum due to the inclusion of CSB and CSB ′ B samples, respectively.…”
Section: Papermentioning
confidence: 93%
“…Furthermore, the deconvolution of the Cr (2p 3/2 and 2p 1/2 ) peaks (figure 3(c)) revealed four distinct peaks, demonstrating the coexistence of various Cr oxidation states. Specifically, the peak observed at 576.0 and 585.5 eV corresponds to Cr 2+ , whereas the peaks at 578.9 and 588.2 eV indicate Cr 3+ [13,[69][70][71]. The molar ratio of Cr 2+ to Cr 3+ was determined to be 41%:59%.…”
Section: Xps Analysismentioning
confidence: 95%
“…The O-1 s spectra (depicted in figure 3(d)) were subjected to deconvolution, resulting in the identification of three distinct peaks with binding energies situated at 529.1, 531.1, and 533.5 eV. These three peaks can be attributed to metal-oxygen bonds, oxygen vacancies, and surfaceadsorbed hydroxyl groups, respectively, with the molar ratio of 21%:61%:14% [69]. The oxygen vacancy (61%) of disordered YNCO double perovskite is much larger than the oxygen vacancy (35%) of a similar Dy-based transition metal double perovskite [72].…”
Section: Xps Analysismentioning
confidence: 99%
“…Whereas, the colorless antibiotic CIP does not have visible light absorption properties and cannot take part in photosensitization reactions. 19 Therefore, in this investigation, the efficiency of the catalysts toward colored RhB and colorless CIP degradation was evaluated as a function of solar irradiation. Fig.…”
Section: Photocatalytic Propertiesmentioning
confidence: 99%
“…It is reported that the BiO 7 polyhedron with a dipole moment of 0.174 Debye might minimize electron-hole pair recombination and consequently improve the photocatalytic properties of the catalysts. 19 Notably, the perovskite and sillenite characteristics of bismuth ferrite are influenced by both its intrinsic properties and the flexibility with which those properties can be altered by various synthesis routes and their conditions. Therefore, several synthesis techniques have been developed, including solid-state reactions, co-precipitation, sol-gel, and hydrothermal synthesis, 7,[20][21][22][23] which have demonstrated a substantial impact on influencing the structure and morphology of bismuth ferrite, and consequently its physical properties.…”
Section: Introductionmentioning
confidence: 99%